2005
DOI: 10.1103/physreve.71.036123
|View full text |Cite
|
Sign up to set email alerts
|

Crack propagation in viscoelastic solids

Abstract: We study crack propagation in a viscoelastic solid. Using simple arguments, we derive equations for the velocity dependence of the crack-tip radius, a (v) , and for the energy per unit area to propagate the crack, G (v) . For a viscoelastic modulus E (omega) which increases as omega(1-s) (0< s< 1) in the transition region between the rubbery region and the glassy region, we find that a (v) approximately G (v) approximately v(alpha) with alpha= (1-s) / (2-s) . The theory is in good agreement with experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
277
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(283 citation statements)
references
References 19 publications
6
277
0
Order By: Relevance
“…Therefore, the tearing energy obtained for a higher velocity at a given temperature has the same value as that measured at the lower velocity and low temperature according to the time-temperature equivalence. 27,28 Following this equivalence, we found that, as shown in Figure 3d, all the tearing energy data measured at different temperatures and crack velocities can be reduced to a nice master curve at a reference temperature (ܶ = 24 ℃) when the the same shift factors ܽ ் and ܾ ் determined from the linear dynamic measurement in Figure 1c and Figure 1d are used, respectively. The result indicates that the equivalence holds for the PA 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 power law relation between the hysteresis energy and stretching strain rate, ܷ ௬௦ ~ ߝሶ .ଷଵ (Figure 2c).…”
Section: Time-temperature Equivalence To Tearing Energymentioning
confidence: 67%
See 2 more Smart Citations
“…Therefore, the tearing energy obtained for a higher velocity at a given temperature has the same value as that measured at the lower velocity and low temperature according to the time-temperature equivalence. 27,28 Following this equivalence, we found that, as shown in Figure 3d, all the tearing energy data measured at different temperatures and crack velocities can be reduced to a nice master curve at a reference temperature (ܶ = 24 ℃) when the the same shift factors ܽ ் and ܾ ் determined from the linear dynamic measurement in Figure 1c and Figure 1d are used, respectively. The result indicates that the equivalence holds for the PA 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 power law relation between the hysteresis energy and stretching strain rate, ܷ ௬௦ ~ ߝሶ .ଷଵ (Figure 2c).…”
Section: Time-temperature Equivalence To Tearing Energymentioning
confidence: 67%
“…Except for the points at high tearing velocity, all the observed crack velocities at various temperatures are slightly lower than the applied tearing velocities over a wide range, as shown in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 velocity ܸ and temperature T, and ߁ is a threshold value of the polymer network below which no fracture occurs. 25,27,28,42,43 During crack propagation, the intrinsic fracture energy of a polymer network involves several complex processes, including chain breaking, cavitation formation, and so on, while the bulk viscoelastic energy dissipation only involves the viscoelastic deformation process around the crack tip.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maugis & Barquins 1978;Maugis 1987;Barthel & Roux 2000;Meitl et al 2006). Such models typically take the form of a powerlaw dependence upon velocity, and a theoretical basis for such phenomenological modelling has been developed by Greenwood & Johnson (1981), Hui et al (1992), de Gennes (1996, Muller (1996), Saulnier et al (2004) and Persson & Brener (2005), among others.…”
Section: Introductionmentioning
confidence: 99%
“…We calculate the crack propagation energy G v , which is an intrinsic material quantity that does not depend on the geometry of the sample, or how the system is loaded: in the following we focus on the simplest case of plane stress [6]. For plain stress, the crack propagation energy G is given by [7] G K 2 =E, where E is the elastic modulus.…”
Section: Hot Cracks In Rubber: Origin Of the Giant Toughness Of Rubbementioning
confidence: 99%